Modeling of soil loss by water erosion in the Tietê River Hydrographic Basin, São Paulo, Brazil - Lense, Guilherme Henrique Expedito; Servidoni, Lucas Emanuel; Parreiras, Taya Cristo; Santana, Derielsen Brandão; Bolleli, Talyson de Melo; Ayer, Joaquim Ernesto Bernardes; Spalevic, Velibor; Mincato, Ronaldo Luiz (Semina: Ciências Agrárias, 2022)
Since the mid-16th century, the Tietê River has been an important route for the territorial occupation and exploitation of natural resources in the interior of São Paulo and Brazil. Currently, the Tietê River is well known for environmental problems related to water pollution and contamination. However, little attention has been focused on water erosion, which is a serious issue that affects the soils and waters of the hydrographic basin. Thus, this work aimed to estimate soil loss caused by water erosion in this basin, which has an area of approximately 72,000 kmÂ², using the Revised Universal Soil Loss Equation (RUSLE). The RUSLE parameter survey and soil loss calculation were performed using geoprocessing techniques. The RUSLE estimated an average soil loss of 8.9 Mg ha-1 yr-1 and revealed that 18% of the basin's territory presents high erosion rates. These are priority zones for conservation practices to reduce water erosion and ensure long-term soil sustainability. The estimated sediment transport was 1.3 Mg ha-1 yr-1, whereas the observed sedimentation, which was calculated based on data from the fluviometric station, was 0.8 Mg ha-1 yr-1. Thus, the results were equivalent considering the large size of the study area and can be used to assist in managing the basin. Estimating soil losses can help in the planning of sustainable management of the Tietê River Hydrographic Basin and highlights the importance of minimizing water erosion, thus helping to prevent additional pollution and contamination with sediments, agrochemicals, and fertilizers.